Special conformal transformations in electrodynamics: mathematical foundations - Călin Galeriu (Revista Brasileira de Ensino de Física)
We review the theory of special conformal transformations, deriving the transformation formulas for some important tensors and tensor densities, to the point where we are able to understand the conformal invariance of Maxwell’s equations. The invariant relativistic action reveals that the rest mass of a particle is a scalar density, while its electric charge is a scalar.